Peptoniphilus faecalis sp. nov., isolated from swine faeces. Issue 6 (14th June 2021) - Ryu, Seoung Woo; Kim, Ji-Sun; Oh, Byeong Seob; Yu, Seung Yeob; Lee, Jung-Sook; Park, Seung-Hwan; Kang, Se Won; Lee, Jiyoung; Lee, Mi-Kyung; Rhee, Moon-Soo; Jung, Hyunjung; Hur, Tai-Young; et al.
Abstract : An obligately anaerobic, Gram-positive, non-motile, coccus-shaped bacterial strain designated AGMB00490 T was isolated from swine faeces. 16S rRNA gene sequence-based phylogenetic analysis indicated that the isolate belongs to the genus Peptoniphilus and that the most closely related species is Peptoniphilus gorbachii WAL 10418 T (=KCTC 5947 T, 97.22 % 16S rRNA gene sequence similarity). Whole genome sequence analysis determined that the DNA G+C content of strain AGMB00490 T was 31.2 mol% and moreover that the genome size and numbers of tRNA and rRNA genes were 2 129 517 bp, 34 and 10, respectively. Strain AGMB00490 T was negative for oxidase and urease; positive for catalase, indole production, arginine arylamidase, leucine arylamidase, tyrosine arylamidase and histidine arylamidase; and weakly positive for phenylalanine arylamidase and glycine arylamidase. The major cellular fatty acids (>10 %) of the isolate were determined to be C16 : 0 and C18 : 1  ω9 c . Strain AGMB00490 T produced acetic acid as a major end product of metabolism. Accordingly, phylogenetic, physiologic and chemotaxonomic analyses revealed that strain AGMB00490 T represents a novel species for which the name Peptoniphilus faecalis sp. nov. is proposed. The type strain is AGMB00490 T (=KCTC 15944 T =NBRC 114159 T ).